Qualidade de vida dos idosos: proposta para o aperfeiçoamento dos indicadores - Furtado, Sandra Regina Sahb (2013)
The Research covers elderlys quality of life indicators, with the intention of discussing and proposing new elements to improve understanding and evaluation of this segments situation. It also contextualizes populational aging and describes elders position both in Brazil and throughout the world. Highlights informations role as key to the dinamics and development of society and as an estrategic resource in decision making. Exposes the scenario of politics towards elderly population and approaches the issue of elderly quality of life and its indicators.